Phytochemical Screening, GC-MS Analysis and Biological Activities of Extracts of Artemisia vulgaris Linn. - Chaudhary, Rashma; Maharjan, Binita; Bharati, Samjhana; Shrestha, Timila; Mishra, Pawan Kumar; Karanjit, Sangita; Bhattarai, Deval Prasad; Homagai, Puspa Lal; Shrestha , Ram Lal Swagat (Amrit Research Journal, 2021)
The aerial parts of Artemisia vulgaris were subjected for successive extraction in solvents methanol, hexane and chloroform, respectively, and compounds present in extract were analysed by GC-MS analysis 12 diﬀerent compounds were found in chloroform extract in which Germacrene was found most abundantly (33.84%). Chloroform extract showed strong antibacterial activity, which was examined against 6 bacteria using the disc diﬀusion method. The IC50 value of chloroform extract accounted for 1.50 mg/mL. The TPC content of the extract was found to be 87.75 mg gallic acid equivalent/g of dry extract, whereas TFC content was found to be 47.25 mg quercetin equivalent/g of dry extract and exhibited LC50 value of 0.18 mg/mL.